Tanggung Jawab Notaris dalam Menjalankan Persekutuan Perdata Notaris - Cinantya Dwestyola; Nada Amira (Majelis: Jurnal Hukum Indonesia, 2024)
Notaries can join together and run a civil partnership together with other fellow Notaries. However, it is explained in the UUJN, the notary civil partnership is not completely the same as the civil partnership contained in the Civil Code. The purpose of this study is to analyze the responsibility of Notaries in carrying out Notary civil partnerships and the impacts caused by the existence of Notary civil partnerships. This research is processed with a normative juridical approach method, namely by looking at law as a set of regulations/rules or doctrines that have a normative nature (law in book). As a result of the problem, each Notary remains individually responsible for what is done and the legal products made as well as the confidentiality of the contents of the deed become the individual responsibility of the Notary and there are positive and negative impacts of the existence of a Notary civil partnership becoming a common concern for Notaries to become members of the Notary civil partnership.